2013
DOI: 10.1007/s11803-013-0203-z
|View full text |Cite
|
Sign up to set email alerts
|

Using experimental data to reduce the single-building sigma of fragility curves: case study of the BRD tower in Bucharest, Romania

Abstract: Sponsor: Vulnérabilité des Ouvrages aux Risques VOR Program, Rhône-Alpes Council. Acknowledgment:This work was supported by the Rhône-Alpes Regional Council (Programme Vulnerabilité des Ouvrages aux Risques) and the Joseph Fourier Université (Grenoble 1).Using experimental data to reduce the single-building sigma of fragility curves: case study of the BRD Tower (Bucharest -Romania) ABSTRACT:The lack of knowledge concerning modelling existing buildings leads to significant variability in fragility curves for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Even if the fifth class corresponding to the strongest values lacks data to have a perfect uniform distribution of PGA, this figure confirms the log-normal distribution assumption, considering to represent the vulnerability of existing buildings through fragility curves, i.e. giving the probability to observe a certain level of damage (through NRRD for example) with respect to ground motion intensity (IMs) (e.g., FEMA, 1999;Milutinovic and Trendafiloski, 2003;McGuire, 2004;Calvi et al, 2006;Michel et al, 2012;Perrault et al, 2013). The same result is observed whatever the IM.…”
Section: Intensity Measures and Building Responsesupporting
confidence: 62%
See 1 more Smart Citation
“…Even if the fifth class corresponding to the strongest values lacks data to have a perfect uniform distribution of PGA, this figure confirms the log-normal distribution assumption, considering to represent the vulnerability of existing buildings through fragility curves, i.e. giving the probability to observe a certain level of damage (through NRRD for example) with respect to ground motion intensity (IMs) (e.g., FEMA, 1999;Milutinovic and Trendafiloski, 2003;McGuire, 2004;Calvi et al, 2006;Michel et al, 2012;Perrault et al, 2013). The same result is observed whatever the IM.…”
Section: Intensity Measures and Building Responsesupporting
confidence: 62%
“…Higher values are expected with higher ground motions, but these values may come from the method, which may not be sufficiently robust. Perrault et al (2013) showed the significant effect of the variation of damping values on fragility functions. Without additional information on the relevancy of this estimate, it is difficult to adopt other solution for setting damping values.…”
Section: Intensity Measures and Building Responsementioning
confidence: 95%
“…The scatter of the results is higher in the case of the C2M model, which can be seen both visually and by comparing the values (0.95 versus 0.81) of the coefficient of determination (R 2 ). A possible explanation for this is the adoption of PGA as an intensity measure [30]. We are proposing an alternative grouping which gives the probability of exceedance of a specific damage state given that the building is in all lower damage states.…”
Section: Structural Period Elongation-based Fragility Curvesmentioning
confidence: 99%
“…Vosooghi et al [17] used data from 32 bridge column test models to develop fragility curves. Perrault et al [18] used experimental data to evaluate the fragility of the BRD tower in Bucharest. Choi et al [19] used RC column experimental results to develop nonlinear models.…”
Section: Introductionmentioning
confidence: 99%